Identification of ungulates used in a traditional Chinese medicine with DNA barcoding technology. Issue 9 (8th April 2015) - Chen, Jing; Jiang, Zhigang; Li, Chunlin; Ping, Xiaoge; Cui, Shaopeng; Tang, Songhua; Chu, Hongjun; Liu, Binwan
Abstract: Horns of Saiga antelope ( Saiga tatarica ) have always been an ingredient of "Lingyangjiao", a traditional Chinese medicine (TCM). Persistent hunting for Saiga antelope has already threatened the survival of critical endangered populations in wild. To control the growing pressure, CITES and Chinese government have legislated for monitoring the trade of Saiga horns. However, similar ungulate horns are difficult to identify by their morphological characteristics, which has impeded the law enforcement. Besides Saiga antelope, other seven ungulate species which have similar horns are also sold and marked as "Lingyangjiao" in TCM markets to offset shortage of Saiga antelope horns. Such species are Gazella subgutturosa, Pantholops hodgsonii, Procapra picticaudata, Procapra gutturosa, Procapra przewalskii, Capra hircus, and Ovis aries . Our study aimed at implementing DNA barcoding technology to diagnose Saiga horns and the substitutes. We successfully extracted genomic DNA from horn samples. We recovered COI sequences of 644 bp with specific primers and 349 bp with nested PCR primers designed for degraded horn samples. The mean interspecific genetic distance of data set of the 644‐bp full barcodes and the 349‐bp mini‐barcodes was 14.96% and 15.38%, respectively, and the mean intraspecific distance was 0.24% and 0.20%, respectively. Each species formed independent clades in neighbor‐joining (NJ) phylogenetic tree of the two data sets with >99% supporting values, except P. gutturosa and P. przewalskii . The deep genetic distances gap and clear species clades in NJ tree of either full barcodes or mini‐barcodes suggest that barcoding technology is an effective tool to diagnose Saiga horns and their substitutes. Barcoding diagnosis protocol developed here will simplify diagnosis of "Lingyangjiao" species and will facilitate conservation of endangered ungulates involved in TCM "Lingyangjiao" markets, especially the Saiga antelope. Abstract : "Lingyangjiao", a traditional Chinese medicine (TCM), was specified to be horns of Saiga antelope, but recently horns of the other seven species were sold as substitutes in TCM markets. Difficulty of diagnosis of these similar horns impeded not only management of trade of Saiga horns but also conservation strategies for these endangered species. We extracted genomic DNA from horns samples and implemented DNA barcoding technology to diagnose species whose horns were sold as "Lingyangjiao" in TCM markets.